2006
DOI: 10.1038/sj.tpj.6500357
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis in a murine model of allergic asthma reveals overlapping disease and therapy dependent pathways in the lung

Abstract: Accumulating evidence in animal models and human asthma support a central role for IL-13 signaling in disease pathogenesis. In order to identify asthma and therapy associated genes, global transcriptional changes were monitored in mouse lung following antigen challenge (ovalbumin (OVA)), either alone or in the presence of a soluble IL-13 antagonist. Changes in whole lung gene expression after instillation of mIL-13 were also measured both in wild type and STAT6 deficient mice. A striking overlap in the gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…However, there are contradictory opinions on the exact role of AMCase in asthma. AMCase gene expression is increased during allergen challenge in ova-sensitized mice (Zhu et al, 2004;Follettie et al, 2006). These observations led to the hypothesis that AMCase contributes to the pathogenesis of Th2 immune responses (Zhu et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, there are contradictory opinions on the exact role of AMCase in asthma. AMCase gene expression is increased during allergen challenge in ova-sensitized mice (Zhu et al, 2004;Follettie et al, 2006). These observations led to the hypothesis that AMCase contributes to the pathogenesis of Th2 immune responses (Zhu et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…In humans and mice it is expressed at high levels in the stomach, and is also expressed in the lung, where it is further induced upon antigen stimulation (Boot et al, 2001;Zhu et al, 2004;Follettie et al, 2006). In a mouse model of asthma, blockade of AMCase prevents lung inflammation and airway hyperreactivity (AHR) (Zhu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Shibamori and colleagues (37) used Der f extract in repeated intranasal sensitizations, and observed increased AHR after a single challenge with 100 mg of Der f. Tournoy and Schou (26) achieved increased AHR in this strain by sensitizing mice with Der p 1 plus alum with a chronic challenge protocol (Days [14][15][16][17][18][19][20]. Importantly, others showed that the addition of adjuvant, namely alum, initiates a distinct inflammatory response involving the inflammosome (38).…”
Section: Discussionmentioning
confidence: 99%
“…Hence 34% (54/161) of the genes were shared by both strains. The list of shared genes includes Arg1, Agr2, Clca3, Muc5ac, Ccl8, Ccl11, Chi3L3, Chi3L4, Chia, Scin, Retnla, Retnlb, Timp, Ear11, Mgl1, Saa3, Serpina3n, and Slc6a24, which were previously described in murine studies (15)(16)(17)(18)(19)(20)(21)(22), adding further support to a role for these genes in allergic airway disease. A subset of these genes was evaluated and confirmed by quantitative RT-PCR (Table E4).…”
Section: Gene Expression Analysis Reveals Shared and Distinct Patternmentioning
confidence: 99%
“…Using animal models of allergic airway disease, investigators applied DNA microarrays to identify potential regulators of asthmatic airway inflammation such as C5 (3), ARG1 (4), ADAM8 (5), SPRR2 (6) as well as to explore the pathways activated by IL13 and STAT6 during the development of allergen-induced lung inflammation (7)(8)(9). Transcriptional analysis of the response to IL-13, allergen challenge, syncytial virus infection, and corticosteroids in epithelial cells identified multiple and rarely overlapping genes (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%